The Totalising Nature of Secure and Forensic Mental Health Services in England and Wales - Markham, Sarah (Frontiers in Psychiatry, 2021)
This evidence-based opinion piece explores the totalising risk averse nature of secure and forensic mental health services and associated iatrogenic harms in England and Wales. Drawing on the research literature I consider the various influences, both external and internal which impact on the provision of such services and how both the therapeutic alliance and recovery potential for patients may be improved. Especial attention is paid to the deployment of restrictive practice, practitioner attitudes, the potential for non-thinking, and how these may impact on decision-making and the care and treatment of mentally disordered offenders.